SIFAT MEKANIS SERAT ENCENG GONDOK SEBAGAI MATERIAL KOMPOSIT SERAT ALAM YANG BIODEGRADABLE - Sri Hastuti; Catur Pramono; Yafi Akhmad (Universitas Tidar, 2018)
The Eichornia crassipes fiber have potentially as a composite reinforcing material. The advantage of composites with natural fibers like to light weight, corrosion resistance, water resistance, attractive performance, and without machining process. The purpose of using natural fiber as an alternative material to replace glass fiber composite material with Eichornia crassipes fibers are friendly and cheap. The research material used Eichornia crassipes fiber, NaOH, Etanol, and H2O. Processing of Eichornia crassipes fiber is washing with water, natural drying ± 10 days in eviromental, fiber taking with steel brush. Dry fibre were subjected to 10%, 20%, 30% NaOH and ethanol solution with variations of immersion time of 2, 4, 6 hours, neutralization with H20, and drying at room temperature. The Single fiber tensile test specimens were made with variations of treatment type in NaOH and Ethanol solution (10%, 20%, 30%), immersion time of 2, 4, and 6 hours. Single fiber test specimens refer to standard ASTM D 3379. Optimum tensile strength test results on NaOH treatment 20% variation of immersion time 4 hours: 28.402 N / mm2 and on ethanol treatment 20% variation of immersion time 2 hours: 48.197 N / mm2.Keywords: eichornia crassipes fiber, composite, single fiber, tensile strength